Analisis Kesalahan Fonologi dalam metode Iqra’ di TPA Alfiah Abbas - Sani, Nurhikmah; Rahmatan, Madah; Pratama, M. Ridho; Alvio, Depaty; Alzikry, Vikky (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
Phonology in learning requires special attention because if errors are found in the pronunciation of sounds, it will affect the purpose of the speech, therefore phonology is very important to study, researchers aim to analyze phonological errors in the iqra method at TPA Alfiah Abbas where this study focuses on the sound of hijaiyah letters. Researchers wanted to know the factors of phonological errors in the iqra method at the Alfiah Abbas landfill and wanted to know how educators could overcome these errors. In this study, the research method used is descriptive qualitative method. The result of this study is the phonological error factor in the pronunciation of hijaiyah letters at Alfiah Abbas landfill due to the different backgrounds of students, such as some students in Alfiah Abbas have memorized short surahs but have not been able to pronounce hijaiyah letters properly and correctly, and due to difficulties in pronouncing some of the same letters and sounds. So teachers use several methods to make it easier for students to memorize and recognize sounds properly and correctly such as using the iqra method and singing methods in their learning.